GE_GERICHTE P/17187/2012 vom 24. November 2015 - GE Cour de justice (2015)
MODIFICATION DE LA DEMANDE; ADMINISTRATION DES PREUVES; DÉNONCIATION CALOMNIEUSE; PEINE COMPLÉMENTAIRE | CPP.399.4; CPP.404.2; CPP.389.1; CP.303; CP.49.2